Pengaruh Relationship Marketing terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan pada PT Astra Internasional - Wibowo, Herry Arianto Lestari (Universitas Brawijaya, Indonesia, 2009)
At this global era each, every company make every effort to continue to improve satisfaction to its customer, so thatcan win emulation and give service to its customer, to its product which more certifiable, especially service product. Repair effort and completion of satisfaction of consumer can be conducted with various strategy, one of the strategy able to be guided to reach for and improve satisfaction of consumer is marketing relationship. Data which is used in this research is primary data obtained by giving quesioner at AUTO Toyota service user 2000 and have subscribed to minimize during one year have, age to more than 17 year and living in Surabaya region. Technique analysis data use diagram path to see causality relation. Result of research concluded that there are positive influence of marketing relationship to satisfaction of customer at International PT Astra. For the satisfaction of customer have an effect on positive to customer loyality at International PT Astra Keywords: Quality Of Service, Satisfaction of Costumer, Consumer loyality